EFFECTS OF FACTOR XIII DEFICIENCY ON THROMBOELASTOGRAPHY. THROMBELASTOGRAPHY WITH CALCIUM AND LYSIS BY ADDITION OF STREPTOKINASE IS MORE SENSITIVE THAN SOLUBILITY TESTS - Marta E Martinuzzo (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Homozygous or double heterozygous factor XIII (FXIII) deficiency is characterized by soft tissue hematomas, intracranial and delated spontaneous bleeding. Alterations of thromboelastographic (TEG) parameters in these patients have been reported. The aim of the study was to show results of TEG, TEG Lysis (Lys 60) induced by subthreshold concentrations of streptokinase (SK), and to compare them to the clot solubility studies results in samples of a1 year old girl with homozygous or double heterozygous FXIII deficiency. Materials and Methods: Case: A one year girl with history of bleeding from umbilical cord. During her first year of live several hematomas in soft upper limb tissue after punctures for vaccination and a gluteal hematoma appeared. One additional sample of a heterozygous and three of acquired FXIII deficiency were also evaluated. Materials and Methods: clotting tests, von Willebrand factor (vWF) antigen and activity,  plasma FXIII-A (pFXIII-A) subunit were measured by an immunoturbidimetric assays in a foto-optical coagulometer. Solubility tests were performed with Ca2+-5 M urea and thrombin-2% acetic acid. Basal and post FXIII concentrate infusion samples were studied. TEG was performed with CaCl2 or CaCl2 + SK (3.2 U/mL) in a Thromboelastograph. Results: Prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin time, fibrinogen, factor VIIIc, vWF and platelet aggregation were normal. Antigenic pFXIII-A subunit was < 2%. TEG presented a normal reaction time (R), 8 min, prolonged k (14 and11min), low Maximum amplitude (MA), 39 and 52 mm,  and Clot Lysis (Lys60) slightly increased (23 and 30%) at diagnosis and post FXIII concentrate infusion (pFXIII-A= 37%), respectively. In Sample at diagnosis clot solubility was abnormal, 50 and 45 min with Ca-Urea and thrombin-acetic acid, respectively, but normal (>16 hours) 1 day post FXIII infusion. Analysis of FXIII deficient and normal plasma mixtures (< 2 -102% of pFXIII-A), showed that Ca-urea solubility was abnormal at pFXIII-A < 9%, thrombin-acetic acid at pFXIII-A<18%, but TEG MA and elasticity at 23% and Lys60 with SK at pFXIII-A< 40%. Conclusions: TEG parameters MA and elasticity, and Lys 60 in TEG with Ca2+ and in TEG Ca2+ and SK are more sensitive to low levels of pFXIII than solubility tests. The increased Lys60 induced by subthreshold concentration of SK could probably reflect the clot characteristics “in vivo” in many patients with pFXIII levels between 5-40% and could be potentially considered as screening test.